Teaching Accountability - الزيون, أحمد; أبو ملحم, محمد حسني (جامعة الوادي - University of Eloued, 2023)
This study puts forward a perspective of the teaching accountability system in order to improve the performance of the university teaching staff as universities in many countries of the contemporary world are in need of a teaching accountability system that enables them to improve their teaching out comes, and also enhance to the performance of their staff in terms of the teaching methodology and evaluation of the academic performance, the activities of the scientific research, the services of local community of the teaching staff of the contemporary universities. The study comes up with a proposed perspective that includes a philosophy, objectives and scientific basics, requirements and mechanisms of realizing this proposed perspective.
A Socio-educational Approach To Improve The Performance Of The University Staff Members
مقال
Keywords: Socio-Socio-educational Performance; University Staff Members. Socio-educational Perspective